2014
DOI: 10.1038/nrneph.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

B cells with immune-regulating function in transplantation

Abstract: In transplantation, the contribution of B cells to the rejection or acceptance of the allograft is a topic of major interest. The presence of donor-specific antibodies in transplant recipients is often associated with decreased graft function and rejection, clearly indicating a pathogenetic role of B cells in transplantation. However, data from studies in humans and rodents suggest that under certain conditions, B cells have the capacity to control or regulate the immune response to a transplanted organ. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 93 publications
1
50
0
Order By: Relevance
“…B cells with regulatory properties are of increasing interest in kidney transplantation, in particular clinical outcomes and phenotypes associated with transitional B cells characterized by surface CD19þCD24hiCD38hi expression (5)(6)(7)(8)(9)(10). This study shows that increased frequencies of these transitional B cells are associated with protection from episodes of BPAR in unselected low/medium immune risk transplant recipients followed longitudinally from the time of transplantation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…B cells with regulatory properties are of increasing interest in kidney transplantation, in particular clinical outcomes and phenotypes associated with transitional B cells characterized by surface CD19þCD24hiCD38hi expression (5)(6)(7)(8)(9)(10). This study shows that increased frequencies of these transitional B cells are associated with protection from episodes of BPAR in unselected low/medium immune risk transplant recipients followed longitudinally from the time of transplantation.…”
Section: Discussionmentioning
confidence: 78%
“…A subset of IL-10 secreting cells with regulatory properties has been identified within the transitional B cell compartment, characterized by the surface phenotype CD19þCD24hiCD38hi, which may protect from autoimmune disease such as systemic lupus and multiple sclerosis (3,4). In kidney transplantation, the importance of CD19þCD24hiCD38hi cells is highlighted by patients who are ''tolerant'' to their graft, who display increased frequencies of these cells (5)(6)(7)(8), although proof as to their direct role in this phenomenon is lacking. Following these landmark studies, 2 subsequent casecontrol, cross-sectional investigations (9,10) revealed associations between reduced CD19þCD24hiCD38hi frequencies and transplant rejection, albeit mainly in the context of antibody-mediated rejection (ABMR) many years following transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…A regulatory function for B cells has been demonstrated in multiple mouse models of autoimmunity and transplantation, whereby indiscriminate B-cell depletion or deficiency paradoxically caused worsening of disease outcomes (66,(91)(92)(93)(94)(95). In each case, the regulatory function could be attributed to IL-10 production by a small subset of B cells.…”
Section: Bregsmentioning
confidence: 99%
“…37 In the inflammatory context, some B cell subsets have shown regulatory properties that rely on either secretion of antiinflammatory cytokines (IL-10) and/ or contact-dependent mechanisms. The fine equilibrium between these two roles of B cells should also be taken into account when discussing immunosuppressive strategies.…”
Section: Immune Mechanisms Underlying Dsa Generationmentioning
confidence: 99%